Resistance of Syagrus coronata fibers in waterproof-coated natural geotextiles under environmental degradation - Holanda, Francisco S. R.; Santos, Luiz D. V.; Sussuchi, Eliana M.; Pedrotti, Alceu; Santos, José F.; Silva, Emersson G.; Fontes, Cátia S.; Araujo Filho, Renisson N. (Frontiers in Sustainability, 2025)
IntroductionSoil mass instability on steep slopes presents significant challenges for erosion control and soil stabilization, requiring the development of biodegradable geotextile alternatives. This study aimed to evaluate the resistance of geotextiles produced from Syagrus coronata (Mart.) Becc. fibers, treated with waterproofing resin, subjected to the effects of exposure to degradation under environmental conditions.MethodsGeotextile samples were exposed to solar radiation, rain, wind, and soil microorganisms; mechanical behavior was assessed via tensile strength and static puncture tests, supplemented by scanning electron microscopy. Statistical analyses, including ANOVA-RM and regression models, were applied to discern the effects of exposure time and resin treatments on the fibers’ performance.Results and discussionKey findings indicate that a single-layer resin treatment significantly prolongs the mechanical viability of the fibers over 120 days, maintaining higher ultimate tensile strength compared to untreated or double-layer-treated fibers. Although double-layer resin provided an initially higher tensile resistance, it accelerated structural failures beyond 90 days, while untreated fibers were nonviable after 60 days. These results highlight a trade-off between stiffness and durability, evidencing that a single-layer resin application delivers an optimal balance of mechanical resilience and flexibility. These findings suggest that a single-layer resin treatment provides a balance between durability and mechanical performance, making it a suitable choice for eco-friendly geotextile applications. Properly treated Syagrus coronata fibers emerge as an economical and sustainable alternative for geotextiles, offering greater durability and contributing to improving slope stabilization and erosion control in environmental conditions of recovery and revegetation of degraded areas.